PERBEDAAN PENGUASAAN KONSEP HIDROKARBON ANTARA MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DENGAN TIPE NUMBER HEAD TOGETHER SISWA MAN PRINGSEWU 2011/2012 - Yayuk Novita Ningrum; Emmawaty Sofya; Ila Rosilawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
The purpose of this study was (1) to describe the existence of hydrocarbon material difference between the mastery of concepts Cooperative Learning with NHT type and TPS type MAN Pringsewu students and (2) the average mastery of concepts which higher hydrocarbons between Cooperative Learning with NHT type and TPS type. The population in this study were all students of class X MAN Pringsewu academic year 2011/2012. Samples were taken using purposive sampling technique. Retrieved class X. 2 as a class experiment I conducted NHT cooperative learning model type, and class X. 4 as a class II experiments conducted cooperative learning model TPS type. The research design using a design-Only Matching Posttest-Only Control Group Design. Analysis of data using normality test, homogeneity of the two variances, and differences in the two trials showed average. The results showed (1) There is a difference between students' mastery of concepts Hydrocarbons who received NHT and Cooperative Learning TPS type. (2) Average Hydrocarbon between student mastery of concepts that use Cooperative Learning TPS type higher than students who use learning NHT type. Keywords: Mastery of the concept, model type NHT Cooperative Learning, Cooperative Learning Model SMT type.